The added value of knowledge management systems to the organization’s performance and efficiency over the existing information systems - Al-qudah, Fadi; AL-hakeem, Sohair; Bani-Hani, Walid (International Journal of Scientific Research and Management (IJSRM), 2021)
Information systems are widely used in organizations and play a very important role in improving an organization’s performance. In recent years knowledge management has become an important issue for managers, consultants and researchers. This paper describes definition and attribution of management information system and knowledge management. It clarifies points like data, information, process, information systems, management information systems and knowledge management system. The approach of this research is to analyze both systems in order to identify their role in an organization, the relationship between them, discover common and uncommon features between the two systems, determine the added value of knowledge management system to the organization’s performance and efficiency over the existing information system and to find out when an information system becomes a knowledge management system and when it is useful to implement the latter.